The fédération internationale de football association (FIFA) 11+ shoulder injury prevention program: awareness, implementation and opinion of worldwide soccer goalkeepers and goalkeepers` coaches - Al Attar, W. S. A.; Yamani, S. A.; Alharbi, E. S.; Ghulam, H. S. H.; Sanders, R. H. (British Journal of Sports Medicine, 2021)
Background: Soccer goalkeepers are more likely than outfield players to injure their upper extremity. The Fédération Internationale de Football Association (FIFA)11+ Shoulder injury prevention program (FIFA 11+S) was developed to prevent upper extremity injuries. Objective: To assess soccer goalkeepers and goalkeepers' coaches' awareness, implementation, and opinion about the FIFA 11+S injury prevention program. Design: Cross-sectional study. Setting: An online survey for all continental football federations. Patients (or Participants): A total of 722 goalkeepers and goalkeepers' coaches completed the survey. Interventions (or Assessment of Risk Factors): The questionnaire consisted of questions covering the awareness, implementation, and goalkeepers and goalkeepers' coaches' opinion of the FIFA 11+S injury prevention program. Questions development was guided by several authors expert in sport medicine and injury prevention programs. Main Outcome Measurements: The primary outcomes were awareness level, implementation rate, and opinion of the effectiveness of the FIFA 11+S injury prevention program in reducing upper extremity injuries. Results: The vast majority (97.60%) of the participants were goalkeepers. A total of 204 (28.25%) of the participants were aware of the FIFA 11+S injury prevention program, 155 (21.46%) were implementing the FIFA 11+S injury prevention program in their current practice. Participants who implemented the FIFA 11+S injury prevention program reported a positive opinion about the program efficacy, with a score of 8.19±0.93 out of 10. Conclusions: The awareness level was low, but the implementation rate among aware participants was acceptable. Goalkeepers and coaches reported a positive score regarding the effectiveness of the FIFA 11+S injury prevention program in reducing upper extremity injuries.